Circumcision and its effects in Africa - Lawal, Taiwo Akeem; Olapade-Olaopa, E. Oluwabunmi (Translational Andrology and Urology; Vol 6, No 2 (April 29, 2017): Translational Andrology and Urology (Global Urology), 2017)
Male circumcision is one of the most commonly performed procedures in Africa, with a wide variation between the different regions on the practice. This is because circumcision is often done for religious and cultural or traditional reasons, which includes being part of rituals or rite of passage to adulthood. There had been few medical indications for the procedure until the human immunodeficiency virus (HIV)/acquired immune deficiency syndrome (AIDS) pandemic, which is prevalent in many of the countries in the region. Evidence from randomized controlled trials conducted in the continent had shown that male circumcision could be instrumental to reducing the transmission of HIV/AIDS in heterosexual couples in high disease prevalent and low circumcision prevalent areas. This had led to the roll-out of large population-based adult male circumcisions as well as the development of tools to facilitate the procedure. Circumcision, however, is not without complications and the incidence appears related to the age of the patient, where the procedure was done, technique used and level of proficiency of the practitioners. This article reviews the practice of circumcision in Africa and highlights the impact of the procedure on the continent.